Neighbourhood renovation concept - A. V. Manko; V. A. Vinogradova; M. I. Voropaeva; A. A. Ganshina; O. S. Matyukhova (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. For many decades there have already been attempts, and sometimes very successful, to create unique urban areas. But these areas were developed mainly as single variants on the formation of urban environment. Basically, they built areas of multi-story buildings according to the average requirements for the comfort of the urban environment. In the modern world, these areas no longer meet the requirements of living and require renovation in accordance with the modern concepts of comfortable living. A study based on Russian and foreign urban planning projects of renovation of areas with mass multi-story buildings is presented.Materials and methods. Based on the analysis of domestic and foreign urban planning experience in the formation of comfortable living environment in the districts and neighbourhoods of large cities, a conceptual project of comprehensive renovation of urban areas of mass construction of 1960s–2000s is proposed.Results. On the example of the Lesoparkovaya metro area the concept of renovation of the area, creation of more comfortable living environment, attraction of holidaymakers, new residents, workers to new jobs to the areas by creating a structure — attractor with development of underground space is presented. Presented two concepts of this structure will attract people to visit the district and use public transport, namely — metro Lesoparkovaya, Butovskaya line.Conclusions. The presented concept can serve as a baseline for the renovation of neighbourhoods with mass development. This requires a so-called attractor, which will attract certain segments of the population, as well as a comprehensive development of the whole neighbourhood. It is necessary that the concept of the neighbourhoods should not be repeated and should be unique. Therefore, everyone will be able to find a rest area, living and working area according to their interests.